2019
DOI: 10.1002/anie.201904404
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of (+)‐Aquatolide and Related Humulanolides

Abstract: The short, efficient total synthesis of (+ +)-aquatolide was achieved by ab iomimetic transannular [2+ +2] photocycloaddition, and provides the first example of constructing a5 /5/4/8-ring system from asteriscunolides.F urthermore,t he reaction leading to a5 /4/4/7-ring system, the originally proposed structure of aquatolide,w as also developed. This strategy achieved syntheses of five more humulanolides,( À)asteriscunolides A, C, D, and I, and (+ +)-tetradehydroasteriscanolide.Supportinginformation and the OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 47 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…In 2019, Takao and coworkers reported a concise total synthesis of (+)-aquatolide (111) by a biomimetic transannular [2 + 2] photocycloaddition to build up its cyclobutane subunit at the late stage (Scheme 16). 47 Their synthesis commenced with vinyl iodide 103, which was readily prepared from known alcohol 101 in 76% yield over four steps. The subsequent ring-opening/ringclosing/cross-metathesis (ROM/RCM/CM) reaction of 103 proceeded in a cascade manner to produce the desired aldehyde.…”
Section: [2 + 2] Photocycloadditionmentioning
confidence: 99%
“…In 2019, Takao and coworkers reported a concise total synthesis of (+)-aquatolide (111) by a biomimetic transannular [2 + 2] photocycloaddition to build up its cyclobutane subunit at the late stage (Scheme 16). 47 Their synthesis commenced with vinyl iodide 103, which was readily prepared from known alcohol 101 in 76% yield over four steps. The subsequent ring-opening/ringclosing/cross-metathesis (ROM/RCM/CM) reaction of 103 proceeded in a cascade manner to produce the desired aldehyde.…”
Section: [2 + 2] Photocycloadditionmentioning
confidence: 99%
“…Initial investigations revealed that a productive reaction occurred to generate what was originally thought to be the desired [5]‐ladderane 26 with good yield and enantioselectivity when the oxazaborolidene 25 was used. However, upon rigorous structural determination by X‐ray crystallography of a derivative ( 30 ), it was revealed that the [2.1.1]‐bicycle 27 was formed as the exclusive product! This remarkable transformation is proposed to occur by initial [2+2] cycloaddition to generate the desired cycloadduct 26 as outlined in Scheme . However, because of the inherent ring strain, a retro‐[2+2] cycloaddition occurs rapidly to generate the chiral allenoate 28 .…”
Section: Resultsmentioning
confidence: 99%
“…However,u pon rigorous structural determination by X-ray crystallography of ad erivative (30), it was revealed that the [2.1.1]-bicycle 27 was formed as the exclusive product! [11,12] This remarkable transformation is proposed to occur by initial [2+ +2] cycloaddition to generate the desired cycloadduct 26 as outlined in Scheme 5. However, because of the inherent ring strain, ar etro-[2+ +2] cycloaddition occurs rapidly to generate the chiral allenoate 28.U pon C À Cb ond rotation and crossed-[2+ +2] cycloaddition (via 29), the observed product 27 could be formed.…”
Section: Research Articlesmentioning
confidence: 99%
“…Aquatolide (C 15 H 18 O 3 ) was a subject of numerous structural investigations (see the most recent study [21] and work cited therein, and also references [22][23][24]). Based on the { 1 H, 13 C} chemical shifts taken from Supplementary Table S3 of reference [24], which were measured in DMSO (dimethyl sulfoxide), the corresponding HETCOR spectrum was simulated by the aforementioned computational approach, of course using DMSO as an implicit solvent in the PCM method.…”
Section: Selection Of the Computational Approachmentioning
confidence: 99%